2019
DOI: 10.1186/s12905-019-0845-8
|View full text |Cite
|
Sign up to set email alerts
|

Coital resumption after delivery among OASIS patients: differences between instrumental and spontaneous delivery

Abstract: BackgroundObstetric anal sphincter injuries (OASIS) are associated with sexual dysfunction and a lower likelihood of sexual activity in the postpartum period. The aim of the present study was to compare coital resumption and the variables influencing this activity after delivery in women with and without a history of obstetric anal sphincter injury (OASIS) and according to the mode of delivery.MethodsA prospective, observational, case-control study was performed at 6 months postpartum in 318 women: 140 with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…These findings have also been proved with a large prevalence at a long-term follow up [ 8 ]. Moreover, a history of OASIS delays the resumption of coital activity among women with spontaneous delivery, reflecting the long-term effects of severe perineal and pelvic trauma on postpartum sexuality [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings have also been proved with a large prevalence at a long-term follow up [ 8 ]. Moreover, a history of OASIS delays the resumption of coital activity among women with spontaneous delivery, reflecting the long-term effects of severe perineal and pelvic trauma on postpartum sexuality [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the PISQ-12 questionnaire may not be the best questionnaire to identify sexual dysfunction in our cohort of postpartum women. The PISQ-12 is validated to assess sexual function in women with urinary incontinence and/or pelvic organ prolapse, but has previously also been used to evaluate sexual function after vaginal delivery [26,27]. The EpiLeva study was conducted to assess the association of mediolateral episiotomy with levator injury and urogynecological complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Current breastfeeding had no impact on the total PISQ-12 score in our study, whereas Anglès-Acedo et al found a negative association at 6 months postpartum. However, their study was not restricted to primiparous women [3]. Question 4 regarding satisfaction with the variety of sexual activities was difficult to analyze because few women scored for dysfunction.…”
Section: Sexual Functionmentioning
confidence: 99%
“…In a study by Anglès-Acedo in 2019, women with operative vaginal delivery were less likely to be sexually active at 6 months postpartum than women with vaginal delivery without operative assistance [ 3 ]. The importance of vaginal tears and obstetric anal sphincter injuries (OASI) is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation